FORMULAS FOR ESTIMATING THE STIFFNESS OF THE REINFORCED TRUSS - Mikhail Nikolaevich Kirsanov (Современная наука и инновации, 2022)
Derives the exact formulas for the calculation of deflection of statically determinate truss with reinforced bars depending on its size, load and number of panels. Considered uniform loading on the upper belt, bottom and a concentrated force at Midspan. Determined forces in the most compressed and stretched elements. Method of cutting nodes, implemented in the program in the language of computer mathematics Maple is used. To generalize the solution for an arbitrary number of panels involved induction method. The asymptotic properties of the solutions are obtained.